Pioneer Reports of Plant Bacterial Diseases - Moura, Romero Marinho de (Anais da Academia Pernambucana de Ciência Agronômica, 2013)
It was researched historical pioneer papers and presented relevant data about what could have been the real first report on a plant disease caused by a bacterium. On E.F. Smith, proclaimed “The father of the Plant Bacteriology” some of his pioneer papers were commented and above all his involvement with the historic polemic on the bacteria as agent of plant diseases.